(untitled) (REMUNOM, 2025)
The increasing complexity of supply chains requires solutions that integrate agility, predictability, and cost reduction. This study aims to analyze the application of Artificial Intelligence (AI) in a medium-sized bakery industry in Minas Gerais, Brazil, through the implementation of SAP Business One software. The research is applied in nature, with a qualitative and quantitative approach. Semi-structured interviews with the supply chain manager and analysis of indicators before and after system adoption were conducted. Results showed significant improvements: increased inventory accuracy, reduced losses, greater reliability in demand forecasting, and cross-sector integration. It is concluded that AI application in supply chain adds competitive advantage and operational efficiency, being a viable alternative for traditional industries.